Program Asistensi Mengajar di SMA Negeri 2 Sungai Selan sebagai Bentuk Implementasi Program Merdeka Belajar kampus Merdeka - Ayu Lestari; Wenni Anggita (Universita Bangka Belitung, 2023)
Teaching assistance in educational units is a learning activity carried out by students collaboratively with teachers/tutors/facilitators/parents in various educational units in the formal, non-formal and informal education subsystems. Thepurpose of this activity is to provide opportunities for students in the field of education to participate in teaching and deepening their knowledge by becoming teachers or tutors and program assistants in educational units spread across the community. This teaching assistance program is a form of implementation of the University of Bangka Belitung's MBKM which supports university performance indicators. This activity was carried out for 16 weeks at SMA Negeri 2 Sungai Selan